Implementasi Kepemimpinan Instruksional Kepala Sekolah selama Pembelajaran Daring - Anjar Sidi Melawati; Dian Hidayati; Cucu Afriliandhi; Istiqomah Istiqomah (Journal of Education and Teaching (JET), 2022)
The purpose of this study was to identify and analyze the implementation of the principal's leadership during online learning at ABA Kindergarten Sukoharjo, Sleman. This research is a type of qualitative research using a participatory approach. With the descriptive analysis method, the author begins by collecting data systematically and consistently, then analyzed, selected then combined so that conclusions can be drawn using deductive analysis. The results of this study found that the implementation of the principal's instructional leadership during online learning had been carried out well but needed to be optimized in the form of several activities; starting from understanding goals and policies, routinely conducting monitoring and evaluation providing solutions to every problem, so that online learning will be more effective, maximum education services for all students and on the other hand still trying to maintain the quality of learning in schools.